SOME ADDITIONAL SPECIES OF HETEROGONIUM - R. E. HOLTTUM (Research Center for Biology, 1955)
The free-veined indusiate species of Heterogonium Presl and two additional exindusiate species are redescribed. Fire new combinations under this generic name are made.